Validation of a universal DNA extraction method for human and microbiAL DNA analysis. Issue 1 (December 2019) - Alessandrini, Federica; Brenciani, Andrea; Fioriti, Simona; Melchionda, Filomena; Mingoia, Marina; Morroni, Gianluca; Tagliabracci, Adriano
Abstract: The study of microbiomes has enormous potential for forensic science because microorganisms are ubiquitous and particular communities of microbes are often associated with specific processes or environments. With recent advances in microbiome science, new opportunities exist for microbiome technologies in forensic science (PMI estimation, location of clandestine graves, soil analysis and personal identification). Before a new technology is accepted by the forensic science, it requires an initial validation phase. The aim of our study was to evaluate if the DNA IQ™ Casework Pro Kit for Maxwell® 16 (Promega) is suitable for microbial DNA extraction, without modifications. Ten bacterial strains were selected and subjected to the GenElute Bacterial Genomic DNA extraction protocol (Sigma-Aldrich) and to the DNA IQ™ Casework Pro Kit for Maxwell® 16 protocol. Extracted DNA was quantified and submitted to NGS analysis on an Ion S5 NGS System. Data were analyzed using the Ion Reporter Software metagenomics workflow. Our work has shown that it is possible to purify both microbial and human DNA using the Promega kit, thus making it possible to analyze both human and microbial DNA from a single trace, a pivotal factor in forensics where the quantities of biological material available are usually very limited.